Characterization analysis of quality factor, electro-mechanical coupling and spurious modes for AlN Lamb-wave resonators with fs> 2 GHz. (July 2022) - Lv, Shitao; Zhu, Zheng; Long, Fei; Sun, Haiyan; Song, Chenguang; Zhang, Aoyu; Tan, Fazeng; Zhao, Jicong
Abstract: In this paper, a systematical study is performed to analyze the quality factor, electromechanical coupling ( k 2 eff ) and spurious modes of Lamb-wave resonators for the frequency above 2 GHz. The effect of the support tether width on the resonator's performance was studied through theoretical and experimental analysis. By extracting the equivalent electrical parameters of the interdigitated (IDT)-Ground and IDT-Floating resonators, the reasons for their differences in k 2 eff and parallel-resonance quality factor ( Q p ) values were clarified. Moreover, the spurious modes can be effectively suppressed by increasing the number of IDTs and reducing the length proportion of the bottom electrode to the effective electrode. The measurement results show that the optimized IDT-Floating resonator is free of spurious mode, meanwhile its series-resonance quality factor ( Q s ), and k 2 eff values can reach 1371.7, 448.8, and 0.82% at 2.092 GHz, respectively. Moreover, the influence of IDT materials on the resonators' performance was also analyzed.